Preparation of MoS2-polyvinylpyrrolidone nanocomposites for flexible nonvolatile rewritable memory devices with reduced graphene oxide electrodes - Liu, Juqing (2013)
A facile method for exfoliation and dispersion of molybdenum disulfide (MoS2) with the aid of polyvinylpyrrolidone (PVP) is proposed. The resultant PVP-coated MoS2 nanosheets, i.e., MoS2-PVP nanocomposites, are well dispersed in the low-boiling ethanol solvent, facilitating their thin film preparation and the device fabrication by solution processing technique. As a proof of concept, a flexible memory diode with the configuration of reduced graphene oxide (rGO)/MoS2-PVP/Al exhibited a typical bistable electrical switching and nonvolatile rewritable memory effect with the function of flash. These experimental results prove that the electrical transition is due to the charge trapping and detrapping behavior of MoS2 in the PVP dielectric material. This study paves a way of employing two-dimensional nanomaterials as both functional materials and conducting electrodes for the future flexible data storage.